FLUKTUASI KURS VALUTA ASING DI BEBERAPA NEGARA ASIA TENGGARA - Josephine Wuri (EXERO : Journal of Research in Business and Economics, 2018)
Recently, the fluctuation of trade among countries in Southeast Asia is very fast, especially with the agreement of the Asean Economic Community (AEC) in 2015. It will establish the economic integration in Southeast Asia. This is expected to reduce the gap among the ASEAN countries. Therefore, the trade among countries also raises the fluctuation of foreign exchange rates. This study aims to analyze the factors that influence foreign exchange rates in several Southeast Asian countries. The secondary data used in this research were taken from the International Financial Statistics published by the International Monetary Fund 2012-2014. The data analysis technique used in this research was panel data regression analysis with Fixed Effect Model. The results showed that inflation and interest rates were variables that affect foreign exchange rates in several Southeast Asian countries. It was known that inflation and interest rates had positive effect on foreign exchange rates. It is also known that the depreciation of rupiah against US dollar was the highest compared to the ones of Ringgit Malaysia and Bath Thailand. Furthermore, the study is expected to give suggestion and information for government in those countries in determining monetary policy to overcome the fluctuation of foreign exchange rates.